PENGARUH LIKUIDITAS DAN SOLVABILITAS TERHADAP PROFITABILITAS PADA PT WASKITA KARYA (PERSERO) Tbk PERIODE 2014 - 2023 - Iin Hernawati; Enny Savitri (Journal of Research and Publication Innovation, 2025)
This study aims to determine the effect of Current Ratio and Debt To Equity Ratio on Return On Asset at PT Waskita Karya (Persero) Tbk for the period 2014 - 2023. The type of research used is descriptive quantitative. The data analysis methods used include: Descriptive Statistics, Classical Assumption Test (Normality, Multicolonierity, Hesteroscedasticity, Autocolleration), Multiple Regression Test, Hepotesis Test (partial T Test and simultaneous F Test), Determination Coefficient Test (R2). The results of this study indicate that Current Ratio has a significant effect on Return On Asset at PT Waskita Karya (Persero) Tbk, this is evidenced by tcount = -4.165 < ttable = 2.365 with a significant value of 0.004 <0.05. Debt To Equity Ratio has a significant effect on Return On Asset at PT Waskita Karya (Persero) Tbk, this is evidenced by the tcount 3.007 > ttable 2,365 with a significant value of 0.020 <0.05. Current Ratio and Debt To Equity Ratio simultaneously have a significant effect on Return On Asset at PT Waskita Karya (Persero) Tbk, this is evidenced by Fcount = 13.437 > Ftable = 4.46 with a significant value of 0.004 < 0.05. Contribution of Coefficient determination (R2) Cirrent Ratio and Debt To Equity Ratio is 79.4%, the remaining 20.6% is influenced by other variables not examined in this research.